Antibiotic Resistance in the Drinking Water: Old and New Strategies to Remove Antibiotics, Resistant Bacteria, and Resistance Genes - Ana Catarina Duarte; Sílvia Rodrigues; Andrea Afonso; António Nogueira; Paula Coutinho (MDPI AG, 2022)
Bacterial resistance is a naturally occurring process. However, bacterial antibiotic resistance has emerged as a major public health problem in recent years. The accumulation of antibiotics in the environment, including in wastewaters and drinking water, has contributed to the development of antibiotic resistant bacteria and the dissemination of antibiotic resistance genes (ARGs). Such can be justified by the growing consumption of antibiotics and their inadequate elimination. The conventional water treatments are ineffective in promoting the complete elimination of antibiotics and bacteria, mainly in removing ARGs. Therefore, ARGs can be horizontally transferred to other microorganisms within the aquatic environment, thus promoting the dissemination of antibiotic resistance. In this review, we discuss the efficiency of conventional water treatment processes in removing agents that can spread/stimulate the development of antibiotic resistance and the promising strategies for water remediation, mainly those based on nanotechnology and microalgae. Despite the potential of some of these approaches, the elimination of ARGs remains a challenge that requires further research. Moreover, the development of new processes must avoid the release of new contaminants for the environment, such as the chemicals resulting from nanomaterials synthesis, and consider the utilization of green and eco-friendly alternatives such as biogenic nanomaterials and microalgae-based technologies.